PENGARUH TABUNGAN MUDHARABAH DEPOSITO MUDHARABAH TERHADAP PEMBIAYAAN MUDHRABAH PT BANK SYARIAH PERIODE 2015-2022 - Anisyah, Nur (STAI Bahriyatul Ulum Pandan, Indonesia, 2024)
The purpose of this study was to find out how the influence of mudharabah savings and mudharabah deposits affects the level of financing at BRI Syariah banks. The research method used in this research is quantitative research. By using the casual method to get an explanation of a problem related to cause and effect relationships. The type of data used in this study is secondary data, namely in the form of annual reports or annual financial reports that have been published by Bank BRI Syariah for the period 2015-2022. Data sources are obtained indirectly through financial reports or annual reports. The data collection technique used by researchers in this study was taken through the quarterly financial reports of BRI Syariah Bank for the period 2015-2022. Data analysis technique uses multiple linear regression. The results of the Mudharabah Savings study have a negative and significant effect on BRI Syariah Bank Financing and Mudharabah Deposits have a positive and significant effect on Mudharabah Financing. Together, Mudharabah Savings and Deposits contributed to Mudharabah Financing with a contribution of 35.1%.